Postural analysis of eight university student wheelchair users when performing written exercises in their classroom: A case study in Santiago de Cali, Colombia (2012)
In students with physical disabilities, the more energy and time required and invested into finding a good posture, the longer the learning process takes. For this reason, the objective of this study was to characterize the posture in the act of writing of wheelchair users in a classroom. Eight students, (three women) aged 18-40, of some of the main universities of the city of Santiago de Cali participated. An observational field study filming of approximately 10 minutes was done while they took notes in their classes. Posture of the head, trunk, and upper extremities was analyzed with respect to its axis and the type of movement in each joint. The postures were classified depending on the location of support surface finding five different postures in the eight students. In these five postures some biomechanical risk factors, usually present in wheelchair users, are increased when they are associated with those postures. Those associated risk factors are: possible disc spine deformation, muscular stress and causing of pressure ulcer. In conclusion, in four of these five postures a poor interaction among person, task and work desk was observed. Therefore, seven of the eight students in this study were found to have a posture that could be considered risky